Life histories, current perspectives - Llanos Zuloaga, Martha (2022)
This essay represents an update reflection on the subject of the narrative at the service of the different branches of the human and social sciences. Through a journey to the most important milestones of knowledge in the field of psychohistory, psychobiography, and autobiographies to conclude in life stories as the central point of the theme. Life histories is a method to understand not only better the human being but to facilitate and reinforce the awareness of the importance of the first years of life with the research work of Psychoanalyst Alice Miller. In this publication, we rescue the value of pioneer studies based on life stories such as the sons of Sánchez by Oscar Lewis done in 1965 in Latin America and years later the history about Domitila in Bolivia by Viezzer in 1978. Likewise, share the power of stories worldwide and their contribution in the search for recognition of marginalized populations, in promoting inclusion, social justice and peace. Finally, an acknowledgment of the efforts of the UNIFE Women’s Observatory to disseminate life stories of women whose contributions are relevant and who have sometimes remained anonymous.